"Do You Understand How Racially Motivated This Is?": Institutional Discipline, Double Standards, and Projects of Media Fugitivity. Issue 1 (24th March 2023) - Martin, Marlaina
Abstract: Mainstream imaginaries of success in the United States tend to center white men. This phenomenon, though increasingly criticized, pervades media systems, which have effectively served as major channels to facilitate, disperse, and popularize such ideals globally. Unsurprisingly, then, US mainstream media institutions have not generally favored non‐white and/or non‐men creators. Via code phrases such as best practices and professionalism, racialized and gendered assumptions continue to shape participatory landscapes of media production. Hence, for many Black women enrolled in formal media education and training programs, schooling's disciplinary norms—alongside society's inclination to mark and marginalize Black women as Other—both frustrate and inspire them to develop cunning, culturally mindful approaches that make use of accessible lessons, resources, and networks without abandoning the social issues and objectives that brought them to media in the first place. Framing their flexible methods of resource procurement and repurposing as projects of media fugitivity, this article explores how Black women navigate the overlapping social, technological, and ideological disciplines of institutional subjecthood and cultivate strategies through which to participate in these schooling infrastructures, while at the same time also protecting themselves from them; redistributing gains accrued in them; and selectively challenging hegemonic asks made, norms modeled, and compliances expected in them.